#### notes

The given integral ∫f(x)dx can be transformed into another form by changing

the independent variable x to t by substituting x = g (t).

Consider I =∫ f x dx

Put x = g(t) so that `(dx)/(dt)` = g'(t)

dx = g′(t) dt

Thus I =∫f(x) dx ∫f ( g (t))g'( t) dt

This change of variable formula is one of the important tools available to us in the name of integration by substitution.

#### Video Tutorials

#### Shaalaa.com | Indefinite Integration by U Substitution

##### Series 1: playing of 2

to track your progress

1

0%